Acetaminophen Attenuates invasion and alters the expression of extracellular matrix enzymes and vascular factors in human first trimester trophoblast cells. (15th January 2021) - Burman, Andreanna; Garcia-Milian, Rolando; Wood, Madeleine; DeWitt, Natalie A.; Vasiliou, Vasilis; Guller, Seth; Abrahams, Vikki M.; Whirledge, Shannon
Abstract: Acetaminophen is one of the most common medications taken during pregnancy, considered safe for maternal health and fetal development. However, recent epidemiological studies have associated prenatal acetaminophen use with several developmental disorders in offspring. As acetaminophen can freely cross into and through the placenta, epidemiological associations with prenatal acetaminophen use may reflect direct actions on the fetus and/or the impact of altered placental functions. In the absence of rigorous mechanistic studies, our understanding of how prenatal acetaminophen exposure can cause long-term effects in offspring is limited. The objective of this study was to determine whether acetaminophen can alter key functions of a major placental cell type by utilizing immortalized human first trimester trophoblast cells. This study employed a comparative analysis with the nonsteroidal, anti-inflammatory drug aspirin, which has established effects in first trimester trophoblast cells. We report that immortalized trophoblast cells express the target proteins of acetaminophen and aspirin: cyclooxygenase (COX) −1 and −2. Unlike aspirin, acetaminophen significantly repressed the expression of angiogenesis and vascular remodeling genes in HTR-8/SVneo cells. Moreover, acetaminophen impaired trophoblast invasion by over 80%, while aspirin had no effect on invasion. Acetaminophen exposure reduced the expression of matrix metalloproteinase (MMP)-2 and −9 and increased the expression of tissue inhibitors of matrix metalloproteinases 2, leading to an imbalance in the ratio of proteolytic enzymes. Finally, a bioinformatic approach identified novel acetaminophen-responsive gene networks associated with key trophoblast functions and disease. Together these results suggest that prenatal acetaminophen use may interfere with critical trophoblast functions early in gestation, which may subsequently impact fetal development. Highlights: Acetaminophen impairs invasion of human first trimester trophoblasts cells. Acetaminophen alters expression of proteolytic enzymes in trophoblast cells. Bioinformatics identifies novel gene targets of acetaminophen in trophoblasts.